Colonial Debts : The Case of Puerto Rico - Zambrana, Rocío (Book collections on Project MUSE., 2021)
"Rocío Zambrana uses the current political-economic moment in Puerto Rico to outline how debt functions as both an apparatus that strengthens neoliberalism and the island's colonial relation to the United States."--